Evidence-based veterinary medicine perception by swine veterinarians: a European survey across diverse practitioner profiles - Teixeira Costa, Charlotte; Lebret, Arnaud; Comer, Clémentine; Rose, Nicolas (Frontiers in Veterinary Science, 2025)
Evidence-Based Veterinary Medicine (EBVM) enhances the quality of care by guiding clinical decisions with robust scientific data, leading to more effective disease management. Evaluating the levels of knowledge and use is crucial for identifying gaps and training needs, ultimately promoting the adoption of evidence-based practices and optimizing herd health and productivity. This study aimed to give an overview of EBVM perception, with the goal of raising awareness of this concept and highlighting reservations they face in applying it to decision-making process in swine veterinary practice. A cross-sectional online survey was conducted among European swine veterinarians. Respondent characteristics and knowledge of EBVM were analyzed using descriptive statistics. Associations between demographic variables (country, specialization) and EBVM knowledge were assessed using Chi-square tests with Yates' continuity correction where appropriate. A significant level of 0.05 was applied. Results showed that 68% of veterinarians were familiar with EBVM, with knowledge levels varying by country (p < 0.05) and educational background (p < 0.01). While 82% recognized its practical value, barriers such as limited time, difficulty accessing relevant data, and a lack of decision-support tools hindered implementation. Younger veterinarians and those with less experience expressed more reluctance toward EBVM. Despite these challenges, 90% of respondents believed EBVM improved decision-making, professional confidence, and communication with farmers. However, opinions differed regarding how well EBVM is currently integrated and developed in everyday veterinary practice. These findings highlight the need for enhanced education and structured methodologies to bridge the gap between theoretical knowledge and practical application in herd health management.